2001
DOI: 10.1055/s-2001-14337
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Hepatocyte Protective Activity and the Structure-Activity Relationships of Quinic Acid and Caffeic Acid Derivatives from the Flower Buds of Lonicera bournei

Abstract: 13 quinic acid derivatives along with caffeic acid, methyl caffeate, myo-inositol, bis[5-formylfurfuryl] ether and 6,7-dihydroxycoumarin were isolated from the ethanol extract of the flower buds of Lonicera bournei Hemsl., among which 8 compounds were firstly obtained from this genus. The effects of different solvent soluble fractions of the ethanol extract and the pure compounds on heptocyte death induced by D-galactosamine (D-GalN)/tumor necrosis factor alpha (TNF-alpha) were studied, and the structure-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…These results were in agreement with the conclusions of previous structure-activity relationship investigations by other researchers. [5][6][7]11,15) It was proved that the protein-ligands binding mechanism could be used as a mode to elucidate the biological and pharmacological properties of the ligands. In addition, once the carboxyl groups being esterified, the binding affinities became stronger, which suggested that esterification of carboxyl group also seemed having some effects in the interaction processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in agreement with the conclusions of previous structure-activity relationship investigations by other researchers. [5][6][7]11,15) It was proved that the protein-ligands binding mechanism could be used as a mode to elucidate the biological and pharmacological properties of the ligands. In addition, once the carboxyl groups being esterified, the binding affinities became stronger, which suggested that esterification of carboxyl group also seemed having some effects in the interaction processes.…”
Section: Resultsmentioning
confidence: 99%
“…Most important, CQAs have been established as an important class of compounds with their potential effects of inhibiting human immunodeficiency virus (HIV)-1 integrase selectively and preventing HIV-1 replication in tissue culture at nontoxic concentrations. [12][13][14] Structure-activity relationship studies showed that their antioxidant, 5) antitumor, 6) hepatoprotective 7) and antimutagenicity 11) activities increased in proportion to the number of caffeoyl groups. Recently, it was also concluded that the radical scavenging activity of natural dicaffeoylquinic acids in the biological aqueous system might depend on the positions of caffeoyl ester groups.…”
mentioning
confidence: 99%
“…On this context, it could be said that C. humilis is a good source of quinic acid. Many studies in the literature showed that quinic acid has a potent broad spectrum antioxidant (Pero et al, 2009), hepatoprotective (Xiang et al, 2001) and can be used to combat prostate cancer (Onbathamizh & Padmini, 2013).…”
Section: Most Of the Compounds In Ms Exhibited Abundant [M -H] In Negmentioning
confidence: 99%
“…Lonicera japonica, a twining shrub that grows in East Asia, including Korea, has been used as a superb anti-inflammatory medicinal plant from ancient times. It is also known to have antibacterial, antivirus, antiangiogenesis, painkiller, and liver protection effects [23,24,25]. Chelidonium majus is known worldwide for its medicinal properties, and has lately attracted interest for its anti-inflammatory, antibacterial, immune function, antitumor, liver protection, painkiller, and anticancer effects [26].…”
Section: Introductionmentioning
confidence: 99%